Implementation of Group Guidance Services In Increasing The Motivation of Class XI Online Business and Marketing (BDP) 2 Students At SMKN 1 Kedawung Kec. Kedawung Kab. Cirebon - Nida Nurfadilla (Asesment : Journal Of Counseling Guidance, 2023)
This study aims to determine whether the implementation of group guidance services can increase achievement motivation in grade XI Online Business and Marketing (BDP) 2 students at SMKN 1 Kedawung. In this study the author uses qualitative phenomenological methods, which intends to understand the phenomenon of what theresearch subjects experienced holistically, and  with descriptions in the form of words or language through the process of data collection carried out by observation, literature review, in-depth interviews, and also documentation of the implementation of group guidance services in increasing the motivation of grade XI students in online business and  Marketing (BDP) 2 at SMKN 1 Kedawung. Based on the research that has been done, it was found that the implementation of group guidance services in increasing the motivation of grade XI Online Business and Marketing (BDP) 2 students at SMKN 1 Kedawung was carried out in 3 stages, namely, the preparation stage, the activity stage and the evaluation stage. The implementation of group guidance services is carried out 3 times a week. The implementation of this group guidance consisted of 4 grade XI BDP 2 students who had low achievement motivation using the group discussion method. The implementation of group guidance services provided by Guidance and  Counseling (BK) teachers, is able to increase the motivation of grade XI Online Business and Marketing students at SMKN 1 Kedawung